Tanggung Jawab Pelaku Usaha Terhadap Standar Mutu Kosmetik Bagi Konsumen Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Nofiardi Nofiardi; Iriansyah Iriansyah; Yetti Yetti (Jurnal Selat, 2021)
Consumer protection is all efforts that ensure legal certainty to provide protection to consumers. This study aims to explain the responsibility of business actors to cosmetic quality standards for consumers based on Law Number 8 of 1999 concerning Consumer Protection. The method used in this research is normative legal research. In the decision of the Batam District Court Number 986/Pid.Sus/2016/PNBtm, Miau Kiuk alias Grace, an illegal cosmetic business actor, was sentenced to imprisonment for 4 months and 15 days and a fine of Rp. 5,000,000.00 without any accountability to the consumer. In the decision of the North Jakarta District Court Number 1616/Pid.Sus/2016/PNJktUtr, William Perkasa, an illegal cosmetic business actor, was sentenced to imprisonment for 1 year 6 months and a fine of Rp. 1,000,000,000.00 without any accountability to the consumer. In the decision of the Payakumbuh District Court Number 98/Pid.Sus/2017/PNPyh, Armen Dahlan, an illegal cosmetic business actor, was sentenced to prison for 1 month and a fine of Rp. 3,000,000.00 without any accountability to the consumer. Law enforcement officers should apply maximum sanctions to illegal cosmetic business actors accompanied by accountability to consumers who become victims as regulated in Law Number 8 of 1999 concerning Consumer Protection.